Epidemiological study of animal bite victims and admission in general surgery department, in Southern Odisha: a cross sectional institutional study - Pattanayak, Sibaprashad; Kumar Malla, Tapan; Kishore Bara, Bipin; Kumar Behera, Manoj (International Surgery Journal, 2017)
Background: Human rabies continues to be endemic in India and according to recent estimate 20,000 persons die of this disease every year. Hence this study was conducted to know the prevalence and pattern of animal bites during last one year and to determine the rate of admission in Department of Surgery. Methods: This study was conducted in the casualty, Department of Community Medicine, Department of Surgery at M. K. C. G. Medical College, Odisha, India between 1st April 2016 - March 31st, 2017. It was a cross sectional study, where convenient sampling method was used. The sample size was 6242 subjects, above 1year age group selected randomly within last 1 year. The socio demographic characteristics, epidemiological and rate of admission in surgery department were studied. Results: It was found that during last one year, out of 6242 animal bite cases, majority of them were bitten by dogs 4785 (76.66%). It was found that 5617 (90%) are category III bite, 548 (8.78%) are category II bites, 77 (1.23%) are category I bite. Parts of body bitten by animals were limbs 5828 (93.37%), face 312 (5%), back 52 (0.83%). Out of 6242 cases, 348 (5.5%) cases were admitted in General Surgery Department. Conclusions: The prevalence of dog bite was found to be more and was of category III in nature and part of body affected were mostly limbs. Prevalence of bite was nearly equal among male and female. Around 5% of the total animal bite cases required admission in Department of Surgery.